Design and Implementation of Dustbin with Radiation Detector for Hospital - Raghad Ahmed Sakhil; Sajjad Jabbar Jasim; Ali Feras Mahmoud; Muslim Mukdad Jassim; Noor Mahmoud Taha; Sura Ammar Ahmed (American Journal of Botany and Bioengineering, 2025)
Effective management of radioactive medical waste is critical for ensuring safety in hospital environments. Current waste disposal systems often lack real-time detection capabilities for radioactive contamination, creating a significant knowledge gap in healthcare waste management. This study presents the design and implementation of a smart dustbin integrated with a Geiger-Müller radiation detector, infrared sensors, and GSM communication for automatic identification and classification of radioactive waste. Using an embedded microcontroller system, the dustbin measures radiation exposure levels and alerts personnel via sound and wireless notifications when thresholds are exceeded. Experimental results demonstrate high accuracy in detecting ionizing radiation from medical waste, ensuring safe segregation and disposal. The system has strong implications for enhancing hospital safety, reducing exposure risks, and supporting automated, eco-friendly waste monitoring